Optimalisasi Manajemen Perpusatakaan: Sistem Basis Data Terdistribusi Menggunakan Metode Rapid Application Development (RAD) - PRABOWO, ARY; Qori Halimatul Hidayah; Sharen Ming Sianggara; Desmond Orix Khoermala (STORAGE: Jurnal Ilmiah Teknik dan Ilmu Komputer, 2025)
Library management in secondary schools often faces challenges with centralized database systems, including inefficiency, slow data access, and risk of information loss. This research aims to design a distributed database system to improve the library management performance of SMP XYZ Pekanbaru by addressing these limitations. Using the Rapid Application Development (RAD) method, the study successfully designed a system architecture that not only enhances data access speed and minimizes the risk of data loss but also enables effective data synchronization between library locations. Based on estimates, the system design improves data access speed by up to 30% compared to centralized systems and reduces data synchronization time to an average of 2 seconds per transaction. The proposed data replication architecture is also expected to reduce the central server load by 70% by distributing data requests to relevant locations, ensuring data consistency and increasing system reliability. This research demonstrates that transitioning from a manual to a distributed database system can significantly optimize library management, improve operational efficiency, and enhance the overall user experience.